Bibliometric Exploration of the Role of Cultural Adaptation in Global Marketing Success - Loso Judijanto; Wira Pramana Putra; Muhammad Ammar Muhtadi (Westscience Press, 2024)
This study presents a comprehensive bibliometric analysis of cultural adaptation in global marketing, highlighting key thematic clusters, research trends, potential research topics, and patterns in author collaboration. The analysis identifies significant focus areas, including cultural adaptation, marketing strategy, local adaptation, performance outcomes, and intervention and translation. The research trends reveal a shift from foundational studies on consumer behavior and standardization towards more practical investigations into the implementation and impact of cultural adaptation strategies. Potential research topics are proposed, such as consumer-centric adaptation, balancing standardization and adaptation, organizational capabilities for adaptation, the impact of cross-cultural training, export performance, and the integration of digital and social media. The author collaboration network shows distinct clusters with limited cross-collaboration, suggesting opportunities for more interdisciplinary research. This study provides a detailed overview of the current research landscape and highlights areas for future investigation to enhance the understanding and practice of cultural adaptation in global marketing.